Utilization of complementary and traditional medicine practitioners among middle-aged and older adults in India: results of a national survey in 2017-2018 - Supa Pengpid; Karl Peltzer (BMC, 2021)
Abstract Background Lack of information exists about the use of traditional and complementary medicine (TCM) use among middle-aged and older adults in India, which led to studying the estimates of past-12-month Ayurveda/Yoga/Naturopathy/Unani/Siddha/Homeopathy (AYUSH) practitioner and traditional health practitioner (THP) utilization in India. Methods The study included 72,262 individuals (45 years and older) from the cross-sectional 2017-2018 Longitudinal Ageing Study in India (LASI) Wave 1. Results The prevalence of past 12-month AYUSH practitioner utilization was 6.5%, THP use 7.0%, and AYUSH or THP use 13.0%. The rate of AYUSH practitioner utilization was determined by older age (≥60 years) (Adjusted Odds Ratio-AOR: 1.20, 95% Confidence Interval-CI: 1.07-1.34), having pain (AOR: 1.48, 95% CI: 1.29-1.69), any bone or joint diseases (AOR: 1.57, 95% CI: 1.35-1.82), current tobacco use (AOR: 1.30, 95% CI: 1.12-1.50), male sex (AOR: 0.76, 95% CI: 0.68-0.85), high subjective socioeconomic status (AOR: 0.72, 95% CI: 0.60-0.87), urban residence (AOR: 0.71, 95% CI: 0.57-0.88), diabetes (AOR: 0.66, 95% CI: 0.55-0.81), chronic heart disease (AOR: 0.52, 95% CI: 0.37-0.73), and having a health insurance cover (AOR: 0.36, 95% CI: 0.30-0.44). The rate of THP utilization was determined by depressive symptoms (AOR: 1.17, 95% CI: 1.01-1.35), sleep problems (AOR: 1.28, 95% CI: 1.08-1.51), having pain (AOR: 1.82, 95% CI: 1.55-2.15), current tobacco use (AOR: 1.35, 95% CI: 1.22-1.51), having health insurance cover (AOR: 0.41, 95% CI: 0.33-0.51), hypertension (AOR: 0.82, 95% CI: 0.71-0.95), diabetes (AOR: 0.50, 95% CI: 0.39-0.65), urban residence (AOR: 0.25, 95% CI: 0.19-0.34), and high subjective socioeconomic status (AOR: 0.70, 95% CI: 0.58-0.85). Conclusion A moderate prevalence of AYUSH practitioner and THP use among middle-aged and older adults in India was found and several factors associated with AYUSH practitioner and THP use were identified.